Managing stress principles and strategies for health and well-being - Seaward, Brian Luke (Jones & Bartlett Learning, 2015)
This book provides a comprehensive approach to stress management honoring the integration, balance, and harmony of mind, body, spirit, and emotions. The holistic approach taken by internationally acclaimed lecturer and author Brian Luke Seaward gently guides the reader to greater levels of mental, emotional, physical, and spiritual well-being by emphasizing the importance of mind-body-spirit unity